Hubungan Antara IMT dengan Keluhan Lower Back Pain pada Mahasiswa FK Unisba - Dimas Muhammad Farhan; Dede Setiapriagung; Yuniarti (UNISBA Press, 2023)
Abstract. Low Back Pain (LBP) is a pain complaint that often occurs in the world, especially in Indonesia. Body Mass Index (BMI) is one of the risk factors for someone to experience LBP and there has been no research on the relationship between BMI and LBP complaints in student of the faculty of medicine, Bandung Islamic University. This study aims to analyze whether there is a relationship between body mass index and LBP complaints in FK UNISBA students. This study used an analytic observational method with a cross-sectional approach. The sampling method is by using probability sampling technique with random sampling. The number of samples according to inclusion enumeration was 85 people with measurements including measurements of height, weight and LBP complaints. The average age of the respondents was 18 years old as many as 43 people (50.6%) and based on gender the majority were women as many as 54 people (63.5%). The average BMI of the respondents was in the normal BMI category, namely 35 people (41.2%). LBP complaints to respondents, namely as many as 58 people (68.2%) did not experience LBP complaints. Bivariate analysis using the chi square test obtained BMI results with LBP complaints (p: 0.182) > 0.05 which means that there is no relationship between BMI and LBP complaints in FK UNISBA students. Abstrak. Low back Pain (LBP) merupakan keluhan nyeri yang sering terjadi di dunia terutama di Indonesia. Indeks massa tubuh (IMT) merupakan salah satu faktor risiko seseorang untuk mengalami LBP dan belum ada penelitian tentang hubungan antara IMT dengan keluhan LBP pada mahasiswa FK UNISBA. Penelitian ini bertujuan untuk menganalisis apakah terdapat hubungan antara IMT dengan keluhan LBP pada mahasiswa FK UNISBA. Penelitian ini menggunakan metode analitik observasional dengan pendekatan cross-sectional. Cara mengambilan sampel adalah dengan teknik probability sampling dengan jenis random sampling. Jumlah sampel yang sesuai dengan kriteria inklusi sebanyak 85 orang dengan pengukuran meliputi pengukuran tinggi badan, berat badan dan keluhan LBP. Usia rata-rata responden adalah berusia 18 tahun sebanyak 43 orang (50.6%) dan berdasarkan jenis kelamin sebagian besar perempuan sebanyak 54 orang (63.5%). Indeks massa tubuh rata-rata pada responden adalah kategori IMT normal yaitu sebanyak 35 orang (41.2%). Keluhan LBP pada responden yakni sebanyak 58 orang (68.2%) tidak mengalami keluhan LBP. Analisis bivariat menggunakan uji chi square mendapatkan hasil IMT dengan keluhan LBP (p: 0.182) > 0.05 dengan hal ini disimpulkan bahwa tidak terdapat hubungan antara IMT dengan keluhan LBP pada mahasiswa FK UNISBA.